Assessing the role of triple helix system intermediaries in nurturing an industrial biotechnology innovation network. (20th March 2019) - Barrie, Jack; Zawdie, Girma; João, Elsa
Abstract: The rate of transition to a circular economy would largely be influenced by how successfully sustainable niche innovation can be developed and adopted. This paper measures and evaluates the effectiveness of employing a triple helix-based system intermediary as a policy tool for nurturing a niche innovation network in line with circular economy transition. This was achieved through a complete social network analysis of a national industrial biotechnology innovation network, in which the organization functioning as network manager was innovatively structured as a triple helix-based system intermediary. Through unique access to the entire national industrial biotechnology niche network, a large set of primary data was collected on 13 types of relational ties related to innovation between all 64 public sector, industry and academic niche network member organizations. The impact of the triple helix-based system intermediary on the level of cohesion, presence of cohesive subgroups and centralisation of the niche network was empirically measured. As such, the effectiveness of the intermediary in undertaking key nurturing activities of building the network, facilitating shared learning and raising expectations were evaluated. This allowed for the most comprehensive empirical study to date on a niche innovation network and the role of system intermediaries in circular economy transition. The results of the analysis demonstrate the profound nurturing effect that the introduction of a triple helix-based system intermediary has had on the network. In particular, the results appear to confirm the effectiveness of the intermediary with regards to increasing knowledge and resource flows amongst triple helix institutions as well as between regime and niche actors. Highlights: System intermediation is necessary for nurturing circular economy oriented niche innovation networks. Niche network cohesion, clustering and centralisation increased from presence of triple helix-based system intermediary. Triple helix system intermediary expanded niche network, raised expectations and increased shared learning. Triple-helix system intermediary can broker structural holes between niche and wider regime.